A Research Review of Contemporary Effects on the Economy of Saudi Arabia in the light of the Hadiths of the Prophet Muhammad (SAW) (Journal of Asian Development Studies, 2025)
This article examines Saudi Arabia's (KSA) current economic situation and the effects of politics, religion, culture, and agriculture. It also investigates if the nation's commercial practices are consistent with Islamic teachings, including the Prophet Muhammad's (PBUH) hadiths. The aim of this study is to understand the economic effects and the function of Islamic ideas across a range of industries. Saudi Arabia, a major participant on the world stage, has a robust economy mostly powered by its enormous gas and oil production. Its industries are growing quickly, yet this expansion comes with many difficulties. Economic development, the problems brought on by fast industrialization, and the Islamic viewpoint on domestic trade are all included in this overview. It assesses whether economic activities align with Islamic beliefs and offers insights into the contemporary business world. By examining these elements, the article seeks to provide a thorough understanding of Saudi Arabia's changing economy and the way that business and Islamic values interact in the contemporary world.